PENGARUH KOMPETENSI, PARTISIPASI MANAJEMEN, DAN DUKUNGAN TOP MANAGEMENT TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA KOPERASI DI DESA MENGWI - I Gusti Agung Ayu Manik Sanjani; I Putu Deddy Samtika Putra (UNHI Press, 2021)
This study aims to test and analyze the effect of competence, management participation, and top management support on the effectiveness of accounting information systems. This study uses a survey method by distributing 50 questionnaires to managers and managers of cooperatives in the village of Mengwi. The study population includes cooperatives in the village of Mengwi, amounting to 14 cooperatives, by using 50 samples. To determine the sample used purposive sampling method. Next, the completed questionnaires were analyzed by multiple linear regression. The test results show that competence has a significant positive effect on the effectiveness of accounting information systems. Management participation does not affect the effectiveness of accounting information systems. Meanwhile, top management support has a significant positive effect on the effectiveness of accounting information systems.